Երուսաղեմի կարգավիճակի հարցը ՄԱԿ–ում - Հովհաննիսյան, Արտակ Հ. («Զանգակ - 97»)
Jerusalem has emerged as a major point of contention in Israel's negotiations with its Arab neighbors, particularly the Palestinians. Claims of historic, religious and legal rights to the city have been asserted by the various parties to the eonfliet and, accordingly, these three aspects should be reviewed: The Observation that, "Jerusalem is holy to three religions," tends to mislead, since Jerusalem is holy to Jews, Muslims and Christians in fundamentally different ways. Jerusalem contains sites holy to Muslims and Christians, and is one of many locations of religious significance to them. Israel has advanced a cohercnt case, based upon the preeepts of international law, for sovereignty over Jerusalem. The Palestinians, for their part, have failed to offer any legal grounds in support of their Claim to the city. Their Claim seems to be based solely on their desire to possess it. Throughout history, the Jewish People has maintained a presence in Jerusalem, ever since King David established the city as his capital nearly 3,000 years ago.
Keywords: Պատմություն; Քաղաքականություն